Desenvolvimento de novos produtos e sustentabilidade: um estudo de caso pela ótica de recursos - Horta, Luciana Harumi Hashiba Maestrelli (2013)
Innovation and sustainability within their continuous efforts develop a bilateral relationship in which sustainability depends on innovation and sustainability is also an 'engine' of innovation. The development of new products (New Product Development - NPD) is recognized as one of the main types of innovation, and despite the extensive literature, it still presents challenges for businesses by introducing discontinuity in its operations, requiring greater understanding of how the company reconfigures itself facing strategic change. This study aims to describe how the principles of sustainability are incorporated into the NPD, as a process and as an organizational capacity, through the perspective of resources. A single and exemplary case study of a brazilian company in the cosmetics industry explores this company’s NPD and its changes towards the strategic direction for sustainability. In the case analyzed it is shown how sustainability principles were incorporated into NPD through the perspective of resources, skills and operational capabilities, establishing the relationship between innovation and sustainability. The strategy of sustainability depended on the ability and the process of NPD to be incorporated into the company's operations. Moreover, it shows the specificity of the company Natura, by observing that its culture and vision were clearly related to the principles of sustainability, even before the company itself explicitly adopted this strategic direction. This study aims to contribute to a field not yet explored in the analysis of innovation and sustainability jointly and at the levels of operations and business. It is expected that the six theoretical proposals made in this study will provide opportunities for further studies.